Manhattan Beach [large type] : a novel - Egan, Jennifer (Thorndike Press, a part of Gale, a Cengage Company, 2017)
Manhattan Beach opens in Brooklyn during the Great Depression. Anna Kerrigan, nearly twelve years old, accompanies her father to the house of Dexter Styles, a man who, she gleans, is crucial to the survival of her father and her family. Years later, her father has disappeared and the country is at war. Anna works at the Brooklyn Naval Yard, where women are allowed to hold jobs that had always belonged to men. She becomes the first female diver, the most dangerous and exclusive of occupations, repairing the ships that will help America win the war. She is the sole provider for her mother, a farm girl who had a brief and glamorous career with the Ziegfeld Follies, and her lovely, severely disabled sister. At a nightclub, she chances to meet Dexter Styles again, and she begins to understand the complexity of her father's life, the reasons he might have vanished.